PERAN PENYIDIK BEA CUKAI DALAM PEMBERANTASAN TINDAK PIDANA PENYELUNDUPAN NARKOTIKA PADA KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI SAMARINDA - Jemmy, Jemmy (Journal of Law ( Jurnal Ilmu Hukum ), 2025)
ABSTRACT.Drug abuse can lead to various health, social, and criminal problems that harm society as a whole. Therefore, eradicating drug trafficking must be one of the main priorities in law enforcement in Indonesia. This research analyzes the role of Customs investigators in combating drug trafficking offenses at the Customs and Excise Office of Samarinda and the challenges faced by Customs investigators in combating drug trafficking offenses in the Samarinda area. This study employs normative research, in which normative legal research is a process to discover legal rules, legal principles, and legal doctrines to address legal issues. Customs investigators have the authority regulated by the Customs Law and the Criminal Procedure Code to conduct supervision, investigation, and enforcement against drug smuggling that involves border routes and ports in the Samarinda area. The eradication of narcotics smuggling crimes in the Samarinda area faces various significant challenges, such as limitations in human resources, suboptimal detection technology, and increasingly sophisticated smuggling modalities. Cooperation between Customs, the Police, the National Narcotics Agency (BNN), and other relevant institutions must also be strengthened to ensure better coordination in combating drug smuggling. With these measures, it is hoped that the efforts to eradicate narcotics in Samarinda can become more effective. Keywords: Investigator, Customs, Narcotics.